Dried Fish Livelihoods: Women's Work and the Transformation of Processing at the Tonlé Sap - Cranmer, Colleen (Université d'Ottawa / University of Ottawa, 2026)
The Tonlé Sap, Southeast Asia's largest freshwater lake, is undergoing significant ecological transformations within Cambodia's rapidly developing economy. Over the last three decades, declining fish stocks, driven by overfishing, dam development, climate change, and agricultural intensification, have placed pressure on rural communities dependent on fisheries. At the same time, aquaculture expansion and international market integration are reshaping Cambodia's food systems, introducing new opportunities but also intensifying precarity for those working in micro-scale processing. This thesis investigates how women engaged in dried fish processing experience and respond to these intersecting transformations, situating their labour within wider processes of agrarian change. To understand these transformations, this thesis draws on ten months of fieldwork that took place between November 2022 and July 2024, across multiple fish processing locales. A total of 42 surveys and 145 interviews were carried out at markets and villages, with a focus on Kampong Khleang commune. Field sites were selected based on known information about their production of fish products. Using primarily convenience sampling, the research included semi-structured interviews, market surveys, and participant observation to examine how gendered norms, ecological decline, and economic priorities converge to reshape women's livelihoods. Findings show that women's processing work, while central to household survival and local food economies, is persistently undervalued and rendered invisible. Within the forage fish value chain (FFVC), differentiation is growing, reflecting unequal access to natural and financial capitals. Particularly among micro-scale processors, some are exiting independent production to take up wage labour, while others adapt to resource scarcity by shifting processing techniques, diversifying income sources, or selling forage fish as aquaculture feed. These strategies provide short-term coping mechanisms but reduce women's autonomy, deepen class differentiation, and reinforce structural and gender inequalities. Although farmed fish plays a crucial role in maintaining Cambodia's fish supply as wild-caught fish from the Tonlé Sap declines, those working on the margins, processing dried fish, are being overlooked in policy and governance. Development programs target the dried fish and aquaculture sectors in ways that drive growth and maximize profit, focusing on medium and large-scale enterprises. Uneven development in this emerging bimodal system illustrates how rural micro-scale processors will not benefit from current fishery development strategies. This uneven bimodal structure raises concerns about the commodification of resources, derived from a collapsing ecosystem and what this means for the future livelihoods of micro-scale fish processors and small-scale fish farmers. The thesis argues that development strategies must move beyond broad economic objectives to recognize how governance, ecological change, and gendered divisions of labour interact to reshape roles and livelihood security in the FFVC. In doing so, it contributes to scholarship on agrarian transformation, gendered labour, and sustainable livelihoods by showing how global, national, and local drivers of change are experienced through the everyday work of women. What's happening at the Tonlé Sap shows us that dried fish economies are not just about markets and profit, but about gender, power, and environmental sustainability. Women's labour is central, yet undervalued, and development strategies must confront these inequalities and support fish processors in ways that align with their own livelihood goals and priorities.
Keywords: livelihoods; fisheries; aquaculture; gender; agrarian change; feminist political ecology; Cambodia